"They see you as a different thing": the experiences of men who have sex with men with healthcare workers in South African township communities. Issue 6 (21st November 2008) - Lane, T; Mogale, T; Struthers, H; McIntyre, J; Kegeles, S M
Abstract : Objectives: To describe interactions between men who have sex with men (MSM) and healthcare workers (HCW) in peri-urban township communities in South Africa. Method: Qualitative study using semistructured in-depth interviews and focus group discussions in the Gauteng province townships of Soweto and Mamelodi. 32 MSM were purposively sampled for in-depth interviews and 15 for focus group discussions. Topics explored included identity, sexuality, community life, use of health services and experiences of stigma and discrimination. Results: MSM felt their options for non-stigmatising sexual healthcare services were limited by homophobic verbal harassment by HCW. Gay-identified men sought out clinics with reputations for employing HCW who respected their privacy and their sexuality and challenged those HCW who mistreated them. Non-gay-identified MSM presented masculine, heterosexual identities when presenting for sexual health problems and avoided discussing their sexuality with HCW. Conclusions: The strategies MSM employ to confront or avoid homophobia from HCW may not be conducive to sexual health promotion in this population. Interventions that increase the capacity of public sector HCW to provide appropriate sexual health services to MSM are urgently needed.